The Influence of Islamic Work Culture on Midwives’ Work Productivity: A Case Study at RSUD Dr. Soedirman Kebumen - Sunardi, Sunardi; Kusumawaty, Wulandari; Wijaya, Aqsa; Fauzi , Ali Amali (Yayasan Gema Bina Nusantara, 2025)
The objective is to examine the extent to which Islamic values, such as honesty (sidiq), responsibility (amanah), consistency (istiqamah), wisdom (fathanah), and effective communication (tabligh) are internalized in daily work routines and how they contribute to performance outcomes. A quantitative descriptive-correlational method was applied, involving 57 Muslim midwives working in the Bougenville Unit at RSUD Dr. Soedirman Kebumen. Data were collected using validated structured questionnaires, and analysis was conducted using simple linear regression via SPSS 25. The results revealed that Islamic work culture was implemented at a good level (mean score: 76.7%), and midwife productivity was also rated good (mean score: 75.8%). Regression analysis demonstrated a significant positive relationship (p = 0.02), with Islamic work culture explaining 13.7% of productivity variance (R² = 0.137). These findings highlight the practical implication that integrating Islamic values into human resource policies can enhance work performance and foster ethical professionalism. Institutions with strong religious backgrounds may benefit from aligning their organizational culture with spiritual values to improve service quality and employee well-being.